2020
DOI: 10.3390/rs12213587
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Temporal Predictive Modelling of Sorghum Biomass Using UAV-Based Hyperspectral and LiDAR Data

Abstract: High-throughput phenotyping using high spatial, spectral, and temporal resolution remote sensing (RS) data has become a critical part of the plant breeding chain focused on reducing the time and cost of the selection process for the “best” genotypes with respect to the trait(s) of interest. In this paper, the potential of accurate and reliable sorghum biomass prediction using visible and near infrared (VNIR) and short-wave infrared (SWIR) hyperspectral data as well as light detection and ranging (LiDAR) data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 77 publications
3
21
0
Order By: Relevance
“…However, the higher-yield plots tended to have significantly higher reflectance values in the NIR region (800-1000 nm, Figure 3c,f,i) throughout the growing season. Similar findings were also reported on other crops, such as wheat [70][71][72][73], alfalfa [55,74], sorghum [75], and soybean [21,50,76]. This is because higher NIR reflectance values indicate more chlorophyll within plants, representing greater vegetation vigor and health status [77][78][79].…”
Section: Ground Truth Field Data and Spectral Profilessupporting
confidence: 78%
See 1 more Smart Citation
“…However, the higher-yield plots tended to have significantly higher reflectance values in the NIR region (800-1000 nm, Figure 3c,f,i) throughout the growing season. Similar findings were also reported on other crops, such as wheat [70][71][72][73], alfalfa [55,74], sorghum [75], and soybean [21,50,76]. This is because higher NIR reflectance values indicate more chlorophyll within plants, representing greater vegetation vigor and health status [77][78][79].…”
Section: Ground Truth Field Data and Spectral Profilessupporting
confidence: 78%
“…Comparatively, the RF and SVR models are more prone to the multicollinearity issue. It was also reported in [75,88] that tree-based models such as the RF are easily overfitted with a small training data size and a high feature dimension. It can also be seen from Table 3 that the RF models with 81 VIs outperformed the ones with the full spectra.…”
Section: Estimation Performance By Models and Image Featuresmentioning
confidence: 99%
“…Many studies have demonstrated the value of image-based sorghum phenotyping technologies for assessment of plant growth and development (Neilson et al 2015 ; Batz et al 2016 ; Thapa et al 2018 ; Masjedi et al 2020 ). In this study, the ARIS phenotyping platform was shown to be useful for collecting nondestructive measurements of green plant area (GPA) in sorghum.…”
Section: Discussionmentioning
confidence: 99%
“…The first marked deployment and utilisation of drones was accomplished during World War II, and the first evidence of using drones for agriculture was seen with crop spraying in the 1980s (Radoglou-Grammatikis et al, 2020). The use of drones has proved an efficient and effective technique for field and plot plant phenotyping because of its capabilities in: (1) the required throughput, that is UAVs can collect huge quantities of data 'on demand' (Masjedi et al, 2020);…”
Section: Why Drones?mentioning
confidence: 99%